Effects of VSTEP on Students’ Learning Motivation at Vietnam National Uinversity, Hanoi - Lan, Nguyen Thuy; Nga, Nguyen Thuy (VNU Journal of Science: Education Research; Vol 35 No 4DO - 10.25073/2588-1159/vnuer.4294, 2019)
Assessment plays an important role in teaching and learning process. The use of the Vietnamese Standardized Test of English Proficiency (VSTEP) to assess the English learning outcome of all VNU students has created challenges for learners, lectures and managers. This survey study is carried out to examine the effects of VSTEP on 751 students of VNU. The findings show that VSTEP has significant impact on students’ learning motivation; however, students doubt that the current English programs could help them achieve their learning target. Besides, a number of students perceive the difficulty level of the test based on rumor and do not pay much care about the content and format of the test. This study also proposes recommendations to increase the positive effects of the test to enhance the effectiveness of the teaching and learning process.